2023
DOI: 10.1007/s11104-023-05896-w
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects post removal of a range-expanding shrub influence soil fungal communities and create negative plant-soil feedbacks for conspecific seedlings

Abstract: Aims Soil legacy effects can have long-term impacts on soil microbial communities with implications for plant growth and community structure. These effects are well studied for invasive plants, particularly after removal of invasive species; however, we know less about the soil legacy effects post removal of native range expanding species. Methods We used a controlled greenhouse experiment with a range-expanding sagebrush species (Artemisia rothrockii (Asteraceae)) to determine how multiple metrics of sagebrus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…These findings by Wang et al (2022) draw attention to the interlinked relationship between plant-influenced decomposer biota and plant-soil abiotic conditioning, and overlaps between the homefield advantage hypothesis and plant-soil feedback mechanisms. In the same way, Collins et al (2023) showed that vegetation in contrasting ecosystems within the White Mountains of California, USA, shapes relative abundances of soil fungal guilds differently. Specifically, the fungal community conditioned by the range-expanding sagebrush (Artemisia rothrockii) was likely responsible for the negative effects on conspecific performance which, in turn, could temper its invasiveness outside of its historic range (Collins et al 2023).…”
Section: Mechanistic Insights and Relationships Between Abiotic And B...mentioning
confidence: 83%
See 1 more Smart Citation
“…These findings by Wang et al (2022) draw attention to the interlinked relationship between plant-influenced decomposer biota and plant-soil abiotic conditioning, and overlaps between the homefield advantage hypothesis and plant-soil feedback mechanisms. In the same way, Collins et al (2023) showed that vegetation in contrasting ecosystems within the White Mountains of California, USA, shapes relative abundances of soil fungal guilds differently. Specifically, the fungal community conditioned by the range-expanding sagebrush (Artemisia rothrockii) was likely responsible for the negative effects on conspecific performance which, in turn, could temper its invasiveness outside of its historic range (Collins et al 2023).…”
Section: Mechanistic Insights and Relationships Between Abiotic And B...mentioning
confidence: 83%
“…In the same way, Collins et al (2023) showed that vegetation in contrasting ecosystems within the White Mountains of California, USA, shapes relative abundances of soil fungal guilds differently. Specifically, the fungal community conditioned by the range-expanding sagebrush (Artemisia rothrockii) was likely responsible for the negative effects on conspecific performance which, in turn, could temper its invasiveness outside of its historic range (Collins et al 2023). Collectively, these studies demonstrate the importance of interactions among soil biota and abiotic factors that underpin plant-soil feedback mechanisms.…”
Section: Mechanistic Insights and Relationships Between Abiotic And B...mentioning
confidence: 83%
“…For example, microbially mediated plant-soil feedback generated by a range-expanding shrub has been found to inhibit the performance of conspecific seedlings (Collins et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more researchers have begun examining the potential for native woody encroachers to create legacy effects while in situ and following removal (Eldridge & Ding, 2021 ). For example, microbially mediated plant–soil feedback generated by a range‐expanding shrub has been found to inhibit the performance of conspecific seedlings (Collins et al., 2023 ). If the effect we observed experimentally exists in field conditions, then legacy effects of J. virginiana roots could be considered a mechanism that favors the reestablishment of the species in treated areas.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, network analysis has been applied to investigate the co-occurrence patterns of microorganisms in a variety of environments, including rivers, wetlands, lakes, and soils [14][15][16][17]. The microbial groups are positively or negatively linked, exhibiting cooperative or competitive characteristics [18]. Network analysis can also be used to identify keystone taxa, which are highly connected to other species in the network and may have a considerable impact on the entire microbial community [19][20][21].…”
Section: Introductionmentioning
confidence: 99%